SARCASM IN CONTENTS OF INSTAGRAM ACCOUNT: KOMIKNYEBELIN - Marnike Marpaung; Elisa Betty Manullang; Juli Rachmadani Hasibuan (LINGUISTICA, 2020)
This study aims to analyze the types and the function of sarcasm used in komiknyebelin as the source data account of instagram. The data of this study were taken from the content of komiknyebelin account since August 2018 until July 2019 which randomly selecting comics that found sarcasm in the comics. In analyzing the data, the researcher was conducting by using qualitative method. The result showed the types and the function of sarcasm used in komiknyebelin account. The data were analyzed by using Lamb’s theory about the types of saracasm and Leech’s theory facing the illucotionary functions to find the sarcasm function in the content of komiknyebelin. The researcher found 4 types of sarcasm in the content of komiknyebelin account, they were: brooding sarcasm (2 data), polite sarcasm (2 data), obnoxious sarcasm (12 data) and raging sarcasm (2 data). And the researcher also found 2 types of sarcasm functions, they were collaborative function (8 data) and conflictive function (10 data) from the 18 data comic that used sarcasm found in the content of komiknyebelin account. Keywords:  Instagram, Komiknyebelin, Sarcasm Functions, Sarcasm Types